EVALUATION OF MICROALBUMINURIA IN TYPE 2 DIABETIC AND HYPERTENSIVE PATIENT AND ITS CORRELATION WITH DIABETIC NEPHROPATHY (Journal of Academic Research, 2020)
Background: This represents an important topic to study because Microalbuminuria is only one earliest sensitive predictor for poor renal outcomes in Type 2 diabetes mellitus and essential hypertension. Objective: Specifically, we aim to investigate the Microalbuminuria and its association with hypertension, diabetic nephropathy, and other diabetic complications. Methods: Eighty-six patients with type 2 diabetes mellitus (41male and 45 female) were enrolled with twenty-five healthy donors (10 male and 15 female). Microalbumin in a random morning urine sample was used and the patients were categorized as micro-albuminuria group, macro-albuminuria group, and control group. Microalbuminuria, glycosylated hemoglobin, serum urea, and creatinine were measured by (COBASIntegra400plus). Results: This approach allows a more detailed analysis of some aspects of the Microalbuminuria data that it was significantly higher in male and female type 2 Diabetes Mellitus compared with the control group (P ≤ 0.022) (P ≤ 0.005) respectively. The most significant observation of this study is that systolic blood pressure was increased among the Microalbuminuria group in females (P ≤ 0.0012), also in the Macro-albuminuria group in males (P ≤ 0.0001), and female (P ≤ 0.0012) and diastolic Blood pressure in male (P ≤ 0.0076). By carefully examining the data, it is found that HbA1c was increased in Microalbuminuria and macro-albuminuria patients with Type 2 Diabetes Mellitus (P ˂ 0.0001) in male and female compared to the control group. The result of this study showed significant increase in urea in macro-albuminuria group in female (P ≤ 0.0115) and male (P ≤ 0.0143), and creatinine in male and female (P ≤ 0.0001) however urea and creatinine increased in Microalbuminuria group in male-only (P ≤ 0.009) (P ≤ 0.0003) respectively. On statistical analyses, a strong correlation was found between Microalbuminuria and poor glycemic control in females (R 0.426) also urea in females (r = 0.470) and creatinine in males (r = 0.370) and female (r = 0.716). Conclusion: We have provided further evidence the severity and progression of Diabetes Miletus play an important role in increasing the possibility of diabetic nephropathy and other diabetic complications, regular measurement of Microalbuminuria should delay or prevent the development of end-stage renal disease.